Social Inequities in Private Health Sector Workforce in India: Religion, Caste, Class, and Gender - Rama V. Baru; Seemi Zafar (Caste, 2022)
The health workforce is hierarchical in structure in terms of skill mix and social composition. Most of the studies on the health workforce are focused on the number of personnel in the public sector. The private sector that has a large presence employs a significant percentage of the total health work force but there is little reliable data on the numbers involved. This is largely due to the lack of regulation of the private health services. Apart from the numbers involved in both the sectors, a few studies have shown the relationship between the work and social hierarchy in health services. While the public sector has a more diverse mix of social backgrounds due to affirmative policies, the private sector ownership is mostly dominated by an upper and middle caste-class combine. There is an under-representation of minorities and women as owners of private health services. The gendered nature of work is visible with the middle and lower rungs constituted by mostly women and men from lower caste-class combine. The terms of work, working conditions and wages paid for this category of workers amounts to exploitation with no forum for redressal. This essay draws together some primary work and references to secondary research and anecdotal evidences to build the scenario of social inequities among the workforce in the private health services.